Diaphragmatic Amyloidosis Causing Respiratory Failure: A Case Report and Review of Literature - Aleksey Novikov; Horatio Holzer; Robert A. DeSimone; Ghaith Abu-Zeinah; David J. Pisapia; Tomer M. Mark; Raymond D. Pastore (Case Reports in Oncological Medicine)
Neuromuscular respiratory failure is a rare complication of systemic immunoglobulin light chain amyloidosis. We describe a case of a 70-year-old Caucasian man with multiple myeloma who presented with worsening dyspnea. The patient was diagnosed with and treated for congestive heart failure but continued to suffer from hypercapnic respiratory insufficiency. He had restrictive physiology on pulmonary function tests and abnormal phrenic nerve conduction studies, consistent with neuromuscular respiratory failure. The diagnosis of systemic immunoglobulin light chain amyloidosis was made based on the clinical context and a cardiac biopsy. Despite treatment attempts, the patient passed away in the intensive care unit from hypercapnic respiratory failure. Autopsy revealed dense diaphragmatic amyloid deposits without phrenic nerve infiltration or demyelination or lung parenchymal involvement. Only 5 cases of neuromuscular respiratory failure due to amyloid infiltration of the diaphragm have been described. All cases, including this, were characterized by rapid progression and high mortality. Therefore, diaphragmatic amyloidosis should be on the differential for progressive neuromuscular respiratory failure in patients with multiple myeloma or any other monoclonal gammopathy. Given its poor prognosis, early recognition of this condition is essential in order to address goals of care and encourage pursuit of palliative measures.